Fructose Intolerance: Cause or Cure of Chronic Functional Constipation - Mehek Mehta BS; Mirza Beg MD (SAGE Publishing, 2018)
Functional constipation is a common occurrence in the pediatric population. The link between fructose ingestion and constipation is obscure due to a lack of published data. In this article, we discuss the relationship of fructose tolerance and the development of constipation via a literature review and our single-center experience. A literature review of constipation and fructose ingestion was performed using PubMed. A retrospective chart review from the pediatric gastroenterology clinic, January 2012 to December 2015, was completed, with attention to the relationship of fructose intolerance and its clinical presentations. There were 367 patients who underwent the fructose breath hydrogen test (FBHT), out of which 208 patients had fructose intolerance. Clinical presentations included chronic abdominal pain, chronic diarrhea, chronic constipation, emesis, and nausea. Statistical significance was reached for chronic constipation, emesis, and nausea, being less likely to be found in FBHT-positive patients. Thus, fructose intolerance may help resolve symptoms in patients with chronic functional constipation.